STRATEGI PENGEMBANGAN USAHATANI TERUNG (Solanum Melongena L.) DI DESA PUKDALE KECAMATAN KUPANG TIMUR KABUPATEN KUPANG - Styven Vito Rafael; Paulus Un; Kudji Herewila (Buletin Ilmiah Impas, 2021)
This research was conducted with the aim of knowing how the internal factors of eggplant farming (Solanum melongena L.), to find out how the external factors of eggplant farming (Solanum melongena L.) and to find out how the strategy of developing eggplant farming in Pukdale Village, East Kupang District, Kupang Regency. The location of this research was carried out with the consideration that Pukdale village is one of the eggplant (Solanum melongena L.) farms. Primary data obtained by means of interviews and direct questionnaires with respondents. In this study, the number of samples taken was 32 people. In this study using a SWOT analysis consisting of internal and external factors. The results showed that: (1) the internal strategic factor of strength is 1.991 and weakness is a score of 0.766, which means that the influence of strength is greater than the effect of weakness on eggplant farming. While the difference between the external strategic factors of opportunity is 1.734 and the threat has a score of 0.831, which means that the effect of opportunities is greater than the effect of threats on eggplant farming (2) The Position Matrix is ​​in quadrant I, which indicates that this eggplant farming is strong and has a chance. The strategy given is Aggressive, where there is power to be used to seize profitable opportunities.